2019
DOI: 10.1177/1059840519849477
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of Runaway Behavior Among At-Risk Youth

Abstract: This study examines the factors influencing runaway experiences among at-risk youth. Using the data of 1,743 at-risk youth from the 2016 survey of Korean adolescents’ contact with media usage and harmful environment, a logistic regression analysis was conducted. This study shows that factors associated with the adolescents’ experiences of family relationships, violence victimization, and harmful environment influence the occurrence of runaway behavior in at-risk adolescents. A significant outcome of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Parallel to the studies in the literature, this study also found that running away from home was common mainly in children aged 13-18 and among female children. 32,33 The literature associates running away from home with poverty, living in disadvantaged regions, weak parent-child relationship, lack of parent support, conflicts between parents, and weak parent supervision. [32][33][34][35] Various studies also show that running away from home was associated with dropping out of school, alcohol/substance use, physical, emotional and sexual abuse, bullying, disability, inadequate coping skills, depression, self-harm, suicide, and crime.…”
Section: Femalementioning
confidence: 99%
See 2 more Smart Citations
“…Parallel to the studies in the literature, this study also found that running away from home was common mainly in children aged 13-18 and among female children. 32,33 The literature associates running away from home with poverty, living in disadvantaged regions, weak parent-child relationship, lack of parent support, conflicts between parents, and weak parent supervision. [32][33][34][35] Various studies also show that running away from home was associated with dropping out of school, alcohol/substance use, physical, emotional and sexual abuse, bullying, disability, inadequate coping skills, depression, self-harm, suicide, and crime.…”
Section: Femalementioning
confidence: 99%
“…32,33 The literature associates running away from home with poverty, living in disadvantaged regions, weak parent-child relationship, lack of parent support, conflicts between parents, and weak parent supervision. [32][33][34][35] Various studies also show that running away from home was associated with dropping out of school, alcohol/substance use, physical, emotional and sexual abuse, bullying, disability, inadequate coping skills, depression, self-harm, suicide, and crime. [32][33][34][35] These factors could be either the reasons for running away from home or risks to be encountered after running away from home.…”
Section: Femalementioning
confidence: 99%
See 1 more Smart Citation